A METHOD COMPARISON FOR ESTIMATION OF SERUM CALCIUM AND PHOSPHORUS LEVELS AND THEIR ALTERATIONS IN CHRONIC KIDNEY DISEASE PATIENTS - LORE WILLAERT; DR.VASUDHA K.C; DR.KUSUMA K.S; DR. FILIP DUMONT; DR. ELS VAN MECHELEN; MISS RADHIKA K (International Journal of Pharma and Bio Sciences, 2015)
A method comparison study for estimation of serum Calcium and Phosphorus levels and their alterations in CKD (Chronic Kidney Disease) patients was done. Serum Calcium was estimated by O-cresolphthalein complexone spectrophotometric method and NM - BAPTA autoanalyzer method. Serum Phosphorus was estimated by the Gomorri’s spectrophotometric method and Phosphomolybdate UV autoanalyzer method. The need for the study was to find out which of the two methods was more sensitive, specific, cost-effective and had minimal interferences by other metal ions or if one method was as effective as the other one. The study showed that the NM-BAPTA method was an excellent test to measure calcium while both the methods used for phosphorus measurement were fairly good tests. Out of 151 samples, 78 were of CKD and we found that nearly 30.76% of the CKD patients exhibited hypocalcemia and 33.33% of them exhibited hyperphosphatemia by the autoanalyzer methods.